Catalytic placemaking: how innovative urban interventions can serve as tools for positive systemic change - Rankin, Rachel (Kansas State University, 2019)
Urban revival projects are becoming more desirable and necessary for public departments and designers around the world. A majority of America’s population lives in cities but simultaneously, population gain rates are falling due to suburbanization. Cities need to face the challenges of growing urban and suburban populations in order to make cities pleasant and functional places for people to work, live, and play. Kansas City’s East Side is an area representative of the results historic segregation that have lead to systemic inequality, urban blight, and economic instability. The goal of this research project was to understand innovative urban interventions and how they can serve as tools for catalytic change. Understanding vacant parcels and open spaces and how they can be systemically programmed into an activated, engaged, and livable urban environment. The project was in conjunction with the Kansas City Design Center, and the targeted site was the Prospect Corridor in Kansas City, Missouri. The objectives were to understand site context and conditions, to create a typology of urban interventions, and to then synthesize those results through design development into a project proposal. The results can help people in both bottom-up or top-down fashions to revitalize their communities and achieve long-term goals of neighborhood sustainability. Visualizing how the framework and typology work together to formulate design proposals aids architects, landscape architects, artists, and planners by pulling together various types of data to critically inform the creative process.
Keywords: Urban planning; Catalytic placemaking; Prospect Avenue Kansas City